ORGANISASI KURIKULUM BAHASA ARAB - Rahnang Rahnang (AT-TURATS, 2014)
In the learning process, the curriculum has a very important role, especially for teachers and students. Therefore, to make it easier to implement the curriculum, especially in learning the Arabic language, then it is divided into several systems. In the Arabic language learning, the curriculum system division is then called curriculum organization which consists of two systems i.e. Nazhariyatul Furu’ and Nazhariyatul Wahdah. Curriculum organization is a framework or pattern of the lessons arranged based on specific purposes of educational programs to achieve. In addition, the principle of curriculum organization is that it is arranged to facilitate the process of learning for teachers and students so as to achieve educational purposes effectively and optimally.